Glucosamine increases hyaluronic acid production in human osteoarthritic synovium explants - Uitterlinden, EJ (BioMed Central, 2008)
BACKGROUND: Glucosamine (GlcN) used by patients with osteoarthritis was demonstrated to reduce pain, but the working mechanism is still not clear. Viscosupplementation with hyaluronic acid (HA) is also described to reduce pain in osteoarthritis. The synthesis of HA requires GlcN as one of its main building blocks. We therefore hypothesized that addition of GlcN might increase HA production by synovium tissue. METHODS: Human osteoarthritic synovium explants were obtained at total knee surgery and pre-cultured for 1 day. The experimental conditions consisted of a 2 days continuation of the culture with addition of N-Acetyl-glucosamine (GlcN-Ac; 5 mM), glucosamine-hydrochloride (GlcN-HCl; 0.5 and 5 mM), glucose (Gluc; 0.5 and 5 mM). Hereafter HA production was measured in culture medium supernatant using an enzyme-linked binding protein assay. Real time RT-PCR was performed for hyaluronic acid synthase (HAS) 1, 2 and 3 on RNA isolated from the explants. RESULTS: 0.5 mM and 5 mM GlcN-HCl significantly increased HA production compared to control (approximately 2 – 4-fold), whereas GlcN-Ac had no significant effect. Addition of 5 mM Gluc also increased HA production (approximately 2-fold), but 0.5 mM Gluc did not. Gene expression of the HA forming enzymes HAS 1, 2 and 3 was not altered by the addition of GlcN or Gluc. CONCLUSION: Our data suggest that exogenous GlcN can increase HA production by synovium tissue and is more effective at lower concentrations than Gluc. This might indicate that GlcN exerts its potential analgesic properties through stimulation of synovial HA production.